Ultrasonic Investigations of Molecular Interaction in Binary Mixtures of Benzyl Benzoate with Acetonitrile and Benzonitrile - N. Jaya Madhuri; P. S. Naidu; J. Glory; K. Ravindra Prasad (E-Journal of Chemistry)
Ultrasonic velocity, density and viscosity have been measured in the binary mixtures of benzyl benzoate with acetonitrile, benzonitrile at three temperatures 30, 40 and 50 °C. From the experimental data, thermodynamic parameters like adiabatic compressibility, internal pressure, enthalpy, activation energy etc., were computed and the molecular interactions were predicted based on the variation of excess parameters in the mixture. Also theoretical evaluation of velocities was made employing the standard theories. CFT and NOMOTO were found to have an edge. All the three mixtures have shown out strong intermolecular interactions between the unlike molecules and endothermic type of chemical reaction.